Enhancing Learning Creativity and Computational Thinking through Coding-Based Flipbook Media in Elementary Education - Listyana, I Gusti Agung Ayu Putu; Suarjana, I Made; Antara, Putu Aditya (Universitas Pendidikan Ganesha, 2024)
This study addresses the issue of low learning motivation, limited student understanding of science concepts, and the lack of diverse instructional media in fifth-grade elementary classrooms. These conditions necessitate solutions through interactive and innovative learning approaches. The research aims to design, evaluate the validity, practicality, and effectiveness of coding-based flipbook learning media to enhance students’ learning creativity and computational thinking skills. This study employs a quantitative design using a pretest-posttest control group model. The research subjects consist of 36 fifth-grade students. Data were collected through a learning creativity questionnaire and a computational thinking test. Data analysis was conducted using inferential t-tests to determine significant differences between experimental and control groups. The findings reveal that coding-based flipbook media exhibit high validity and practicality levels and are significantly effective in improving students’ learning creativity and computational thinking skills. These findings provide a relevant solution to the issues of low learning motivation, limited concept understanding, and inadequate instructional media in the classroom. In conclusion, coding-based flipbook media represent an effective and innovative approach to supporting science education in elementary schools.